Community Empowerment Through Optimizing Local Wisdom as a Support for The Value of Economic Life - Nur Hidayah; Syamsul Arifin; Devangga Putra Adhitya Pratama; Kurniawati; Andre Tandi Bamba Dominggus; Aprilia Asharifah Suprapto; Ayuni Nurcahyanti (Trescode Green Organization, 2023)
Community Service (PKM) is an annual program carried out by each university which is an application of the Higher Education Chess Dharma. While the Real Work Lecture (KKN) is an annual program carried out by each university which is an application of the Higher Education Chess Dharma. With the implementation of PKM and KKN, it provides extraordinary benefits for students and the community because the results obtained from the implementation of PKM and KKN are enormous, such as an experience gained by students in the form of how to live with the community properly and much more. The implementation of PKM and KKN with